2013
DOI: 10.1111/1744-7917.12057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of heat shock protein 90, 70 and their transcriptional expression patterns on high temperature in adult of Grapholita molesta (Busck)

Abstract: Grapholita molesta (Busck) is a worldwide insect pest damaging stone and pome fruits. High temperature can significantly affect insect survival, development and fecundity. Heat shock protein (Hsp) genes were speculated to possess a pivotal function in response to high temperature stress. In this study, two full-length Hsp genes, Gmhsp90 and Gmhsp70, were cloned from G. molesta using rapid amplification of complementary DNA ends (RACE). The open reading frames of Gmhsp90 and Gmhsp70 obtained were 2 148 bp and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 27 publications
(33 reference statements)
2
27
0
1
Order By: Relevance
“…One of GmHsp70 members previously uploaded in GenBank JX678981 (Chen et al 2014) showed 84 % similarity of full-length amino acid sequence with the gene we studied. Both our GmHsp70 and the one studied by Chen et al (2014) have a conserved C-terminal motif BEEVD^with a potential binding function, suggesting a role in protein folding/refolding (Michels et al 1999;Vabulas et al 2010). Information on Hsp genes from model species might help to identify functional roles of GmHsps, such as the stress-inducible pattern in other species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One of GmHsp70 members previously uploaded in GenBank JX678981 (Chen et al 2014) showed 84 % similarity of full-length amino acid sequence with the gene we studied. Both our GmHsp70 and the one studied by Chen et al (2014) have a conserved C-terminal motif BEEVD^with a potential binding function, suggesting a role in protein folding/refolding (Michels et al 1999;Vabulas et al 2010). Information on Hsp genes from model species might help to identify functional roles of GmHsps, such as the stress-inducible pattern in other species.…”
Section: Discussionmentioning
confidence: 98%
“…The 12-h enclosed moths (equal numbers of males and females) were therefore kept at −5°C (cold) or 42°C (heat) for 1 and 2 h before recovering at 25°C for 2 h. The 42°C temperature is close to 41°C which Chen et al (2014) previously found to elicit higher expression of Hsp70 and Hsp90 in G. molesta compared to lower temperatures or 44°C. No data have previously been collected on lower limits of adults.…”
Section: Thermal and Diapause Responsive Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the economic importance of G. molesta , at the time of this research, only a limited number of studies had been conducted at the molecular level, including the sequencing of the mitochondrial genome (Gong et al 2012), characterization of two general odorant binding protein genes (Zhang et al 2012), population genetic structure (Kirk et al 2013), transcriptome analysis of sex pheromone glands (Jung and Kim 2014), and characterization of two heat shock proteins (Chen et al 2014). Although these studies generated rich genomic and EST sequence data for G. molesta , it lacked sequence information related to detoxification or other insecticide related genes.…”
mentioning
confidence: 99%
“…For the analysis of the expression of poplar homologs of C 4 photosynthetic enzyme genes, all samples were normalized to the reference gene PsnACTIN2 . The final relative expression was calculated using the formula F = 2 -ΔΔ Ct (Chen et al, 2014). …”
Section: Methodsmentioning
confidence: 99%